2009
DOI: 10.1007/s00068-009-8246-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Outcomes in the Jehovah’s Witness Following Trauma: Special Management Concerns for a Unique Population

Abstract: Although our experience was limited, we found no significant difference in the mortality or morbidity between JW patients who received or abstained from transfusion following major trauma. We should keep in mind that the population was small, in order to extract safe conclusions regarding whether we should transfuse or not transfuse trauma patients. We can, however, see interesting insights on the value of trauma resuscitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…These nutrients are important adjuncts in hemoglobin production and enhance the hemoglobin response to erythropoietin [ 20 ]. In one study, iron supplementation was shown to be beneficial and was strongly considered an adjunct in managing Jehovah’s Witness patients [ 21 ]. In the present case, the patient was administered ferrous sulfate, folic acid, iron isomaltoside, and vitamin B12 supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These nutrients are important adjuncts in hemoglobin production and enhance the hemoglobin response to erythropoietin [ 20 ]. In one study, iron supplementation was shown to be beneficial and was strongly considered an adjunct in managing Jehovah’s Witness patients [ 21 ]. In the present case, the patient was administered ferrous sulfate, folic acid, iron isomaltoside, and vitamin B12 supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…In connection with this, careful observation should be performed in patients with coagulopathy and who are on mechanical ventilation. One study showed that the risk of gastric ulcer bleeding increased in this patient group [ 21 ]. Approximately 25% of ICU patients who do not receive prophylactic measures experience gastrointestinal bleeding due to gastric ulcers [ 22 ].…”
Section: Discussionmentioning
confidence: 99%